Dinamika Kemiskinan dan Faktor-Faktor Penentunya: IPM, TPT dan PDRB per Kapita - Fatma Faoziah; Fauzul Adzim (Forum Kerjasama Pendidikan Tinggi, 2026)
The poverty rate in the Barlingmascakeb development region is still quite high when compared to the average poverty rate of Central Java Province, despite improvements over time in the Human Development Index (HDI). This condition suggests that poverty levels are influenced by the Gross Regional Domestic Product (GRDP), the open unemployment rate, and the quality of human development. As a result, it is crucial to investigate these three aspects further. This study's goal is to find out how poverty levels in the Barlingmascakeb development region which includes Banjarnegara, Purbalingga, Banyumas, Cilacap, and Kebumen Regencies are impacted by the Human Development Index (HDI), Open Unemployment Rate (OUR), and Gross Regional Domestic Product (GRDP) between 2010 and 2024. Panel data regression analysis using the Random Effect Model (REM) is used to accomplish this goal. Secondary data gathered from Statistics Indonesia (BPS) is used in the study. The Human Development Index (HDI) significantly reduces poverty levels, as indicated by a coefficient of -3.053429 (p<0.001). Conversely, there is a 0.100918 (p=0.014) link between rising poverty levels and rising unemployment rates (TPT). Furthermore, GRDP has a substantial and adverse effect on poverty, with a value of -0.184018 (p=0.005). The findings demonstrate that the variables under investigation have a considerable impact on poverty levels in the Barlingmascakeb region. In the meantime, poverty is positively and significantly impacted by the open unemployment rate. These results imply that strategies aimed at reducing poverty should concentrate on strengthening economic sectors that can sustain more equitable economic growth, increasing employment opportunities, and enhancing human resource capability.